Population Dynamics in Nepal Over 100 Years (Patan Pragya, 2020)
Population dynamics is the branch of life sciences that studies short-term and long-term changes in the size and age composition of populations, and the biological and environmental processes influencing those changes. The main aim of this article is to analyze the size, distribution, change, growth, trend, pattern and other over all status of population of Nepal of last hundred years (1911 – 2011).Secondary information obtained by author from authentic and reliable different sources and rearranged- calculated, re-tabulated and analyzed and make meaningful and sensible of them. Number of populations are almost 5 fold increased during the (1930 – 2011) 80 years period of time. The population growth rate and doubling times are fluctuation. CDR, CBR, IMR, CMR, MMR are decreasing as increasing of the socio economic development in Nepal. Life expectancy, literacy rate, active age population rate are increasing. The identification of the caste/ethnic groups are rapidly increased, only 60 caste/ethnic groups were identified in 1991, it has increased and reached 100caste/ethnic groups in 2001 and 125 caste/ethnic groups in 2011 census. Population dependency ratio of child is decreasing and increasing of the old age dependency ratio. If old age population growth rate will remaining the same the old age dependency ratio will be increased by 3 fold till 2050. Almost60 percent populations are living in urban duelers. The CBS of Nepal is going to conduct the census in beginning of 2078 BS and expected total population to be more than 31.5 millions.